Relationship between CML and Io’s phase according to Jupiter’s actual radio storms observations - Abood, Kamal M. (Iraqi Journal of Physics, 2019)
The actual observations for Jupiter radio storm were taken for Hawaii station within multi years from 2001 to 2012. The Central Meridian Longitude (CMLІІІ) and Io’s phase (γIo) were calculated for each year from Radio Jove program, the results of CMLІІІ for year 2006 was A=(180-300)º,B=(15-239)º, C=(60-280)º, phase was A=(182-260)º,B=(40-109)º, C=(200-260)º, which were close to the theoretical values, longitude was A=(180-300)º, B=(15-240)º, C=(60-280)º and phase was A=(180-260)º,B=(40-110)º and C=(200-260)º.